Two Heads Are Better Than One-Entrepreneurial Continuous Learning through Massive Open Online Courses - Agnieszka Żur (MDPI AG, 2020)
Globalisation and digital technology have changed the means and mechanisms of knowledge acquisition. The rapidly expanding open-access online resources and various digital learning platforms present new opportunities in the area of continuous entrepreneurial learning, including that of corporate employees. This paper draws on knowledge spillover theory in order to explore the potential of Massive Open Online Courses (MOOCs) as enablers of knowledge exchange, consolidation and new knowledge creation through connecting geographically and institutionally distant actors. The research design is based on a qualitative interpretative approach exploiting a triangulation of methods by using sets of quantitative data collected from MOOC participants, five focus group interviews and text content of online course discussion groups. This study contributes to our understanding of how digital technologies enable entrepreneurial learning on a massive scale. It identifies three factors which can trigger intense horizontal knowledge spillovers on a massive scale: (i) participants’ common interests and aspirations, (ii) induced mobilisation, and (iii) participants’ optional anonymity. Additionally, the findings of this study provide useful information for potential MOOC creators regarding the design and delivery of MOOCs targeting a high density of participant interactions.